Kinetic Control of a Self‐Assembly Pathway towards Hidden Chiral Microcoils. Issue 31 (7th May 2019) - Guo, Yongxian; Liu, Yin; Gong, Yanjun; Xiong, Wei; Zhang, Chuang; Zhao, Jincai; Che, Yanke
Abstract: Manipulating the self‐assembly pathway is essentially important in the supramolecular synthesis of organic nano‐ and microarchitectures. Herein, we design a series of photoisomerizable chiral molecules, and realize precise control over pathway complexity with external light stimuli. The hidden single‐handed microcoils, rather than the straight microribbons through spontaneous assembly, are obtained through a kinetically controlled pathway. The competition between molecular interactions in metastable photostationary intermediates gives rise to a variety of molecular packing and thereby the possibility of chirality transfer from molecules to supramolecular assemblies. Abstract : Pathway complexity was achieved by chiral molecule1, which produced chiral expressed single‐handed microcoils by photoinitiated kinetic controlled self‐assembly, pathway B, or ribbon‐like architectures obtained by spontaneous self‐assembly, pathway A, without chiral expression. Distinct competition of molecular interactions among π–π interactions, steric interactions, and chirality transfer is the mainspring of the pathway differentiation (see scheme).